Exploring Corporate Governance and Firm Value: A Comprehensive Bibliometric Analysis Study - Ervina Dian Ayu Kencana; Arni Surwanti (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study conducts a bibliometric analysis to explore the relationship between corporate governance and firm value. Utilizing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework and Scopus-indexed data, the review includes 856 publications published between 2015 and 2024. The United States and the United Kingdom emerge as the most prolific contributors to this research area. Using VOSviewer for network visualization, the analysis highlights the most influential scholars, including David Yermack, Theodore Eisenberg, Stefan Sundgren, Martin T. Wells, Allen Ferrell, Hao Liang, and Luc Renneboog. Key seminal works identified include Higher Market Valuation of Companies with a Small Board of Directors, Larger Board Size and Decreasing Firm Value in Small Firms, and Socially Responsible Firms. The review further reveals three dominant thematic clusters: agency theory, firm value, and board of directors, which collectively form the conceptual backbone of the corporate governance–firm value discourse. These findings offer a concise roadmap of the field’s foundational theories and serve as a reference point for future researchers seeking to navigate the most influential contributions.